Abstractions for Oversubscription Planning - Mirkis, Vitaly; Domshlak, Carmel (Proceedings of the International Conference on Automated Planning and Scheduling, 2013)
In deterministic OSP, the objective is to achieve an as valuable as possible subset of goals within a fixed allowance of the total action cost. Although numerous applications in various fields share this objective, no substantial algorithmic advances have been made beyond the very special settings of net-benefit optimization. Tracing the key sources of progress in classical planning, we identify a severe lack of domain-independent approximations for OSP, and start with investigating the prospects of abstraction approximations for this problem. In particular, we define the notion of additive abstractions for OSP, study the complexity of deriving effective abstractions from a rich space of hypotheses, and reveal some substantial, empirically relevant islands of tractability.